PROCESSING OF TEMPE LIQUID WASTE IN STAGES USING COMBINATION OF COAGULATION AND ELECTROCOAGULATION METHODS - Lia Cundari; Faisal Akbar Adin; Asyeni Miftahul Jannah; Dyos Santoso (Konversi, 2022)
The purpose of this study was to determine the effect of slow stirring time of flocculation and stress on the electrocoagulation process on turbidity levels and pH values of tempe liquid waste. The research method used is a combination of coagulation and electrocoagulation processes carried out in batches. Variations carried out were slow stirring time of flocculation (10, 15, 20, 25 and 30 minutes) and variation of voltage (3,6, and 9 volts). The results showed that the stirring time and electrocoagulation voltage affected the turbidity of the tempe liquid waste but did not affect the pH level of the tempe liquid waste. The best slow flocculation time was 20 minutes with a turbidity yield of 31.04 NTU and a percent removal of turbidity of 91.56%. The electrocoagulation voltage of 9 volts resulted in a turbidity of 2.01 NTU and a percent turbidity removal of 93.52%.